HUBUNGAN MINAT BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN SE KECAMATAN KUTOARJO TAHUN AJARAN 2019/2020 - Hanaan Rofiiqoh; Tri Saptuti Susiani; Ratna Hidayah (Universitas Sebelas Maret, 2020)
The study aimed to prove positive correlation between interest in learning and mathematics learning outcomes to fifth grade students of public elementary schools in Kutoarjo sub-district in academic year of 2019/2020 and to determine the contribution of interest in learning to mathematics learning outcomes to fifth grade students of public elementary schools in Kutoarjo sub-district in academic year of 2019/2020.The research was quantitative correlational study. Sampling method was cluster random sampling technique with application of the Statistical Product and Service Solution (SPSS) version 16. The samples were 300 fifth grade students in thirteen public elementary schools in Kutoarjo sub-district. Data collection techniques were questionnaires and test. Data analysis used correlation test of Pearson product moment with a significance level of 0.05 and adjusted R square. The correlation test showed Sig.= 0.000 (sig. <0.05). It meant that there was positive and significant correlation between interest in learning and mathematics learning outcomes. It indicated that the higher interest in learning, the higher mathematics learning outcomes and vice versa. Interest in learning contributed 20.91% to mathematics learning outcomes.